Low grade mandibular myxofibrosarcoma in an adult - Carlos Juan Puig González; Juan Carlos Puig Chong; Lianet Castro Bolano (Centro Provincial de Información de Ciencias Médicas, 2022)
The clinical case of a 61-year-old patient, with a history of good health, treated at St. Paul's Milennium Medical Hospital in Ethiopia for presenting, for 2 years, a lesion in the marginal gum, with bulging of the gums, is described. both cortices, which extended from the lower right to the left first premolar, for which it was decided to admit him to the Maxillofacial Surgery Service for study and treatment. It was a rare and large tumor, with extensive lymph node dissemination to levels IV and V in both parts of the neck, so the surgical procedure was performed. The evolution was favorable in the immediate postoperative period and he was discharged from the institution 7 days later, but continued with radiotherapy. And follow-up by outpatient service for 24 months afterwards.